Factor V Leiden Thrombophilia Causing Recurrent Thrombosis (Bangladesh Critical Care Journal, 2021)
Normal hemostasis requires a delicate balance between the natural procoagulant and anticoagulant systems. Thrombophilia is an abnormality of the coagulation or fibrinolytic system that results in a hypercoagulable state and increases the risk for thrombotic event by forming intravascular thrombus. The predisposition to form such blood clot may be inherited or acquired. In inherited thrombophilia, there is deficiency of natural anti-coagulants, e.g. anti-thrombin III, protein C and S or increase formation of human coagulant factors, e.g., factor V Leiden or prothrombin gene 20210A. Factor V Leiden thrombophilia is extremely rare in Bangladesh. We report this unique case of a young lady of 46-year-old presented with continuous headache and found to have extensive cerebral venous thrombosis with bilateral 6th cranial nerve palsy. She had suffered from acute arterial occlusion of left upper limb in September 2016, 2 years prior to current presentation. We suspect thrombophilia according to her presentation. The subsequent step is to screen for-human natural anti-coagulant factors deficiency or presence of mutated form of factor V (factor V Leiden) and prothrombin gene mutation. We screened for and found to have presence of factor V Leiden in our patient. We always should remember that, thrombotic events are increasingly recognized as a significant source of mortality and morbidity, so screening should be considered in selected individuals if criteria suggests.Bangladesh Crit Care J September 2021; 9 (2): 104-108